Macrophage Depletion Protects against Cigarette Smoke-Induced Inflammatory Response in the Mouse Colon and Lung - Lim, Dahae; Kim, Woogyeong; Lee, Chanju; Bae, Hyunsu; Kim, Jinju (Frontiers in Physiology, 2018)
Cigarette smoke (CS) is considered as a major risk factor for pulmonary and intestinal inflammation. CS leads to macrophage infiltration in the mucosae of the lung and colon, inducing the uncontrolled secretion of inflammatory mediators, and thus promoting inflammatory response. In this study, we investigated whether macrophage depletion modulates cigarette smoke (CS)-induced inflammatory response in both the lung and colon. The mice were exposed to CS for 30 min, after which they were rested in a fresh air environment for 30 min. The total duration of exposure to CS was 2 h per day for 4 weeks. Macrophage depletion state was made with the injection of clodronate containing liposome. Individual body weights were measured twice a week, and the mice were sacrificed on day 28. Hematoxylin and eosin (H&E) staining was performed in the lung and colon tissue to determine histological changes. Inflammatory mediators' synthesis was analyzed using ELISA and western blotting. Clodronate liposome treatment ameliorated pathological changes associated with the infiltration of immune cells in the lung and colon. Also, clodronate liposome injected mice showed significantly lower level of inflammatory mediators, including cytokines and chemokine and proteases. Our results indicated that macrophage depletion by clodronate liposome treatment attenuates CS-induced inflammatory response in both the lung and colon.